The COVID-19 Pandemic and Its Economic, Social, and Political Impacts (Istanbul University Press, 2022)
The liberal–capitalist governance model, which has been in use for many years, has survived to this day through the dominance of individualization and the market, expanding the private sector, while limiting the state and its services. However, through COVID-19, we have all witnessed the results of this economic system. The fact that countries with the largest economies in the world are unable to provide the most basic sanitary materials needed to effectively fight the epidemic, choosing which patients are to be treated and leaving the rest to die, raises the question of how humane existing systems are. The most successful countries across the globe have continued their economic development strategies, focusing on the sectors that provide superiority and production. Yet, with this structure of long supply chains and globalization collapsing, the need to fill this gap with strict borders and national productivity has become important. States whose functions have weakened, and have had limited service and capacity due to their economies, have faced a major crisis due to this epidemic. With the COVID-19 outbreak, despite economic developments, we have experienced how health services and agricultural production have been pushed to the limit, threatening humanity in an emergency situation. As a result of the epidemic, we once again understand the importance of our own production—especially agricultural production—that will meet basic needs. We have become aware of how important it is to provide public health services and produce items such as masks, respirators, medicines and vaccines. We have once again experienced the fact that the strategic importance of production can change periodically and according to needs, and we have seen that even though we have money, we cannot buy certain products and services. The epidemic has made almost all of us equal spiritually, physically and socially at a global level. It has created a new awareness in all areas including health, education, income inequality, poverty, unemployment, migration, the climate crisis, and access to basic human needs. The epidemic has nourished selfishness in one sense, and reduced solidarity. It has caused loneliness, medical as well as psychological problems, and information pollution. The epidemic has taken the fear of death from the individual and spread it through society. On the other hand, it has increased the need for solidarity and strengthened our common sense of fate. Therefore, our need for understanding based on social cohesion has gained more importance. Therefore, there is an increased need for restructuring that will prevent social disruption and panic. After 1980, the state shrank in relative terms due to the neoliberal effect in Turkey. The global epidemic has come along at a time of economic and social problems. However, thanks to our general health insurance, the number of hospitals, the number of hospital beds, the potential we have in our country and our ability to manage a crisis, we are facing the epidemic under better conditions. However, despite this, there is an increasing need for restructuring that will enable our country to adapt to the new conditions, survive the crisis with the least damage and meet the needs of the 21st century. What has happened in the economic and social sphere shows that a new paradigm shift is needed. There is an increasing expectation of a paradigm change to build a new economic order based on the principle that needs, wishes, and resources are limited, except for information, rather than the perception of unlimited desires that feed insatiability. In order to survive the process of the crisis with the least damage, it is necessary to restructure industries and the labor markets according to globally rising businesses and professions, all together in solidarity.